Assessing the Livelihood Vulnerabilities and Occupational Hurdles of Street Vendors in Dhaka City - Hasan, Mehedi; Debnath, Shipu; Ali, Sanjida Bintey (The Jahangirnagar Review, 2024)
Street food vending is a common source of livelihood in Dhaka, Bangladesh. However, vendors face various challenges to their well-being and economic security. While previous studies have examined issues faced by street vendors nationally, little research exists on the specific vulnerabilities encountered by those operating in urban slum areas. This mixed methods study aimed to fill this gap by assessing the multidimensional livelihood challenges of 300 street vendors working in Mirpur, Dhaka. Primary data was collected through questionnaires, interviews and focus group discussions. Analysis found vendors earned low and unreliable incomes, experienced health issues from working conditions, and lacked access to social protections. They also faced harassment and restrictions impacting earnings. Support was sought through skills training and stable employment opportunities to improve standards of living. The findings indicate street food vending yields precarious livelihoods for those in slum areas due to multidimensional vulnerabilities. Supportive interventions are needed to enhance income security, social protections, skills development and rights-based recognition for this disadvantaged group.